Molecular Identification of Fusarium proliferatum from toenails: A case report - Gharib, Sazan Jamal; Abdul-razzak Tahir, Nawroz (Kurdistan Journal of Applied Research, 2019)
Fusarium is a saprophytic fungus which is broadly disseminated in soil, plant debris and other organic substrates. These fungi can affect indigenous tissue in immunocompromised patients and result in some fungal infections such as Onychomycosis, bone and joint disease, or sinusitis. In this paper, we report a 56-year-old female has Diabetes milletus who established to disseminate Fusarium infection in her left first toenail from the Dermatology Department / Khabat Skin Center, Sulaimani Province, Iraq. To study of these fungi as the true causative agents of nail infection, we describe a PCR/sequencing assay to confirm routinely diagnosis of the infecting fungi in this case with toenail Onychomycosis. Designation of the ordinary laboratory of Fusarium is very challenging because of the septate hyphae of Fusarium are hard to discriminate from those of Aspergillus, which has a more favourable consequence and this time-consuming. Therefore, molecular tools were used for identification of F. proliferatum from this case by amplifying ITS region of rDNA using a pair of universal primers ITS1 and ITS4. Infectious fungal molecular detection advances the select of right antifungal therapy, in that way improving the medication rate of nails infections. DNA sequence analysis and Phylogenetic tree of the amplified ITS-rDNA was used for species identification of this strain of F. proliferatum. For final identification sequencing of DNA has been carried out by [Macrogen Korea] using forward primer ITS1, The obtained consensus of query sequence was compared with the ITS DNA database on the BLAST homepage, aligned and diagnosed strain deposited to the GenBank and we received an accession number (MK112619). The sequence of the F. proliferatum amplicon was aligned using ClustalW and the alignment was used to make phylogenetic analysis using MEGA software version X. To the best of our knowledge, the isolated Fusarium in this paper is the first case of its kind to be sequenced and reported by the molecular method in Kurdistan region of Iraq